A decision tree model for neuroimmune guidance of allergic immunity. Issue 9 (28th June 2021) - Flayer, Cameron H; Perner, Caroline; Sokol, Caroline L
Abstract: The immune system defends the body from infectious and non‐infectious threats. Distinct recognition strategies have evolved to generate antigen‐specific immunity against pathogens or toxins versus antigen‐independent tissue repair. Structural recognition, or the sensing of conserved motifs, guides the immune response to viruses, bacteria, fungi, and unicellular parasites. Functional recognition, which is sensing that is based on the activities of an input, guides antigen‐independent tissue healing and antigen‐specific Type 2 immunity to toxins, allergens, and helminth parasites. Damage‐associated molecular patterns (DAMPs), released from damaged and dying cells, permit functional recognition by immune cells. However, the DAMP paradigm alone does not explain how functional recognition can lead to such disparate immune responses, namely wound healing and Type 2 immunity. Recent work established that sensory neurons release neuropeptides in response to a variety of toxins and allergens. These neuropeptides act on local innate immune cells, stimulating or inhibiting their activities. By integrating our knowledge on DAMP function with new information on the role of neuropeptides in innate immune activation in Type 2 immunity, we describe a decision tree model of functional recognition. In this model, neuropeptides complement or antagonize DAMPs to guide the development of antigen‐specific Type 2 immunity through the activation of innate immune cells. We discuss why this decision tree system evolved and its implications to allergic diseases. Abstract : Allergens promote the release of damage associated molecular patterns and neuropeptides. The combination of these signals lead to distinct immune responses that can be predicted based on the model described herein.